A Study on Purchase Intention among Customers of Maxis Berhad - editor aibpm; Ban Teoh Kok; Hui Gan Kia; Zhe Pheh Pei; Parthiban Muvintdra; Xiang Tham Yu; Vivian Mei Ying Wong (Advances in Global Economics and Business Journal, 2022)
This study investigates how price, customer satisfaction, and customer loyalty affect the purchase intention among customers of Maxis Berhad. In this study, the quantitative research method was used by distributing the online questionnaire to collect data from 240 customers of Maxis Berhad in Malaysia. The study concluded that customer satisfaction and loyalty have significant positive relationships with purchase intention, whereby the price has a negative relationship with purchase intention among customers of Maxis Berhad. The findings contribute to the increase of subscribers of Maxis Berhad by improving the factors of price, customer satisfaction, and customer loyalty.